Foreign Exchange Committee Master Agreements as International Contractual Standards for Foreign Exchange Derivatives - A. P. Klementyev (Московский журнал международного права, 2023)
INTRODUCTION. The ISDA Master Agreement is possibly the most authoritative cross-border contractual standard in the world of financial markets. It also serves as an example for the local transactional documentation drafters in various countries to regulate the conclusion and performance of over-the-counter derivatives transactions by means of bilateral contracts. However, international master agreements for derivatives and other financial products are not limited to the templates produced by International Swaps and Derivatives Association (ISDA). Foreign Exchange Committee (FXC) suggests a remarkable alternative to the documents maintained by this powerful industry club as far as transactions with foreign currency are concerned.MATERIALS AND METHODS. International Foreign Exchange and Currency Option Master Agreement (IFXCO) and other FXC master agreements served as primary sources of the present article. Its methodological base is represented by general scientific methods (analysis, synthesis, induction, deduction) as well as specific legal research methods. In particular, formal legal method was employed for the literal interpretation of the provisions of FXC standard documentation, historical method was invoked to describe the evolution of standard FXC templates, while comparative legal method was used to undertake a comparative analysis of insolvency laws where appropriate.RESEARCH RESULTS. The article gives a general overview of master agreements in financial markets to put FXC documentation into a broader context of standard contracts publication in financial markets. The analysis of FXC master agreements is carried out through conclusion and performance of FX transactions as well as risk mitigation mechanisms analysis such as close-out netting and collateral. Moreover, the article covers governing law and enforceability issues as well as puts FXC documentation into Russian legal context. Although Russian court, with a high degree of probability, will recognize the choice of governing law made by the parties to the relevant master agreement published by FXC, the enforceability of collateral and close-out netting provisions amidst the bankruptcy of a Russian entity is not secured due to non-recognition of FXC documentation by the Russian authorities.DISCUSSION AND CONCLUSIONS. Author comes to conclusion that despite FXC master agreements are not able to compete with ISDA documentation. However, they are popular with certain financial institutions active in foreign exchange markets. To facilitate the development of Russian financial market the list of recognized master agreements should be broadened by addition of documentation produced by FXC. Arguably, it is necessary to amend these provisions and make them compliant with UNIDROIT as well for the purposes of transactions with banks from the countries considered “friendly” to Russia.